2017
DOI: 10.1093/mnras/stx1617
|View full text |Cite
|
Sign up to set email alerts
|

Baryon effects on the dark matter haloes constrained from strong gravitational lensing

Abstract: Simulations are expected to be the powerful tool to investigate the baryon effects on dark matter (DM) halos. Recent high resolution, cosmological hydrodynamic simulations (Di Cintio et al. 2014, DC14) predict that the inner density profiles of DM halos depend systematically on the ratio of stellar to DM mass (M * /M halo ) which is thought to be able to provide good fits to the observed rotation curves of galaxies. The DC14 profile is fitted from the simulations which are confined to M halo ≤ 10 12 M ⊙ , in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 85 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…These processes include gas accretion, minor mergers, disc dynamics, halo heating, stellar feedback and AGN feedback. The above are typically dependent on galaxy stellar mass and cosmic epoch (Cano-Díaz et al 2016;Abbott et al 2017;Wang et al 2017;Chiosi et al 2017;García et al 2017;Eales et al 2018;Qin et al 2018;Sánchez et al 2018;Cañas et al 2018;Blanc et al 2019) and possibly affect the shape of the σ sSFR -M ⋆ differently. However, it is difficult to study and especially quantify the effect of the different prescriptions important for galaxy evolution to the scatter solely by using insights from observations.…”
Section: Introductionmentioning
confidence: 99%
“…These processes include gas accretion, minor mergers, disc dynamics, halo heating, stellar feedback and AGN feedback. The above are typically dependent on galaxy stellar mass and cosmic epoch (Cano-Díaz et al 2016;Abbott et al 2017;Wang et al 2017;Chiosi et al 2017;García et al 2017;Eales et al 2018;Qin et al 2018;Sánchez et al 2018;Cañas et al 2018;Blanc et al 2019) and possibly affect the shape of the σ sSFR -M ⋆ differently. However, it is difficult to study and especially quantify the effect of the different prescriptions important for galaxy evolution to the scatter solely by using insights from observations.…”
Section: Introductionmentioning
confidence: 99%
“…However, we do note that this study was based on the simulations of four elliptical galaxies that do not represent the entire population. Moreover, there are known inconsistencies between simulated and observed galaxies (Xu et al 2017;Wang et al 2017;Peirani et al 2019), particularly in the core where time delays are sensitive. As such, if this method is to be competitive going forward in to the era of sub 2% estimates on H0, then we will require not only more accurate simulations, but an understanding of the time delay distributions over a larger population than just four volumes.…”
Section: Discussionmentioning
confidence: 99%
“…We return a consistent lens redshift distribution and the estimated masses are both within the expected true mass, and that the model is not particularly sensitive to this parameter. However, we note that there is debate on the reliability of such simulations at reproducing the properties of galaxies, which may impact these results (Xu et al 2017;Wang et al 2017;Peirani et al 2019).…”
Section: Modelmentioning
confidence: 97%
“…First of all, in spite of its larger flexibility compared to more simple lens models, it still allows for most of the interesting properties for lensing studies to be calculated fully analytically, as demonstrated by Du et al (2020). Secondly, contrary to most of the other popular analytical mass models used in lensing, the BPL model has the same global characteristics as the Zhao models, often used to model dark matter haloes (Navarro et al 1997;Hague & Wilkinson 2013Di Cintio et al 2014;Mollitor et al 2015;Tollet et al 2016;Allaert et al 2017;Dekel et al 2017;Wang et al 2017;Katz et al 2017;Cautun et al 2020;Freundlich et al 2020b;Hayashi et al 2020). The fact that the BPL models cannot be supported by an isotropic (or radially anisotropic) distribution function limits the attractiveness of this family of models to some degree.…”
Section: Data Availabilitymentioning
confidence: 99%